Understanding staff-level factors and patient aggression in psychiatric hospitals - Wade, Louise (2017)
Background: The cause of patient aggression is a very complex question, and it continues to be a challenging phenomenon in psychiatric inpatient services. This thesis provides a broad investigation into nursing staff attitudes towards inpatient aggression. Individual factors such as the history of violence are well studied. However, staff-level factors have received less attention. Aims and Objectives: The main purpose of this thesis was to explore and expand the knowledge base of nursing staff attitudes toward patient aggression in secure psychiatric hospitals. The four questions of this thesis were;